Neoadjuvant therapy of cetuximab combined with chemoradiotherapy in rectal cancer: A single-arm meta-analysis of noncomparative clinical studies and randomized controlled trials. Issue 7 (19th February 2021) - Yan, Qi; Zhu, Jun-jing; Zhao, Fang-min; Shu, Qi-jin; Chen, Shu-yi
Abstract: Objective: Preoperative chemoradiotherapy combined with radical resection has reduced local recurrence rates in rectal cancer. Cetuximab shows improvement in rectal cancer treatment. But the role for neoadjuvant therapy of cetuximab combined with chenmoradiotherapy in rectal cancer remains unclear. The present study aimed to use meta-analytical techniques to assess its benefit and risk. Materials and Methods: We searched PubMed, the Cochrane Library, Embase to identify the correlational non-comparative clinical studies and randomized controlled trials (RCTs). The primary endpoints of interest were pathological complete response (pCR), complete response (CR), partial response (PR), stable disease, progressive disease (PD), R0-resection, R1-resection, and R2-resection. The secondary included any grade of toxicity. Results: Eleven investigations (9 noncomparative open-label cohort studies and 2 randomized controlled trials) involving 550 patients were ultimately included. The pooled estimates of pCR was 10% (95% confidence interval [CI]: 7%–13%, I 2 = 55.9%). Simultaneously, only a small amount of patients achieved CR (11%, 95% CI: 7%–15%, I 2 = 44.0%), which was consistent with pCR. Besides, R0 resection (93%, 95% CI: 90%–96%, I 2 = 16.5%) seemed to be increased but need further exploration. The safety was also calculated, and most of the toxicities were moderate. Conclusion: Neoadjuvant therapy of cetuximab combined with chemoradiotherapy could not improve pCR. The raise of R0-resection rate needed to be verified by more high-quality and well-designed RCTs. Meanwhile, the morbidity of toxicity was relatively mild and acceptable. Abstract : Supplemental Digital Content is available in the text